2019
DOI: 10.1111/imm.13054
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33 induces production of autoantibody against autologous respiratory epithelial cells: a potential mechanism for the pathogenesis of COPD

Abstract: Summary The mechanisms underlying the chronic, progressive airways inflammation, remodelling and alveolar structural damage characteristic of human chronic obstructive pulmonary disease (COPD) remain unclear. In the present study, we address the hypothesis that these changes are at least in part mediated by respiratory epithelial alarmin (IL‐33)‐induced production of autoantibodies against airways epithelial cells. Mice immunized with homologous, syngeneic lung tissue lysate along with IL‐33 administered direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…IL-33 increases IL-13 production and results in airway mucus formation. Recently, Li and colleagues [ 17 ] showed that IL-33 induces production of autoantibodies against respiratory epithelial cells, which can be a potential mechanism for inflammation and alveolar destruction in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 increases IL-13 production and results in airway mucus formation. Recently, Li and colleagues [ 17 ] showed that IL-33 induces production of autoantibodies against respiratory epithelial cells, which can be a potential mechanism for inflammation and alveolar destruction in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In the respiratory tract, IL-33 is predominantly released from epithelial cells, alveolar type II epithelial cells, endothelial cells, mast cells, and fibroblasts (Figure ). It serves as an “alarmin” following insult with inhaled stimuli such as allergens, infections, pollution, and cigarette smoke, which results in activation, migration, and recruitment of innate and adaptive immune cells including eosinophils, ILC2s, mast cells, T cells, natural killer T cells, macrophages, dendritic cells, and hematopoietic progenitor cells and production of type 2 (Th2) cytokines including IL-4, IL-5, and IL-13 (reviewed in refs , , and ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, plasma IL-33 levels positively correlate with the peripheral eosinophil count in COPD patients. 16…”
Section: Discussionmentioning
confidence: 99%